Przedświt: fascynacja architekturą mykeńskiej i archaicznej Grecji w Niemczech schyłku XIX i początków XX wieku - Makała, Rafał (Collectanea Philologica, 2024)
At the beginning of the 20th century, German architecture saw a turn towards the art of antiquity, which was partly a reaction to the profusion of decoration in late historicism and Art Nouveau. However, the so-called Reformarchitektur was interested not only in classical antiquity (and the art of classicism and neoclassicism), but also in earlier periods, especially Mycenaean art. This was, of course, related to the discoveries in Troy, Mycenae and Tiryns, but the social and political context of the time was equally important. One of the foundations on which the national identity of the Germans in the 19th century was based was the myth of the ancient Germans, who were supposed to be characterized by courage, sincerity and natural morality. According to the creators of this idea (F. Avenarius, J. Langnehn, A. Haupt, G. Kossinna et al.), the Germans, next to the Greeks, were one of the original peoples of Europe (Urvolk), sharing ideas and artistic forms. In the north of the continent, they were allegedly preserved longer than in the Mediterranean area because the Nordic nations did not take part in the development of mimetic art. Consequently, it was believed that in the architecture of the Mycenaean period, as well as in buildings from the Homeric and archaic periods (as well as in Etruscan and ancient Roman buildings), we could find forms typical of the unpreserved Nordic architecture, destroyed in the process of Christianization. Therefore, Mycenaean and archaic architecture became the subject of interpretation in the spirit of nationalism, perceived, however, in a broader sense than just the framework of one nation. This was related to the category of “Nordic nations” as well as an even broader vision of the “primordial peoples of Europe”. These views and research became one of the inspirations for the architecture created at that time with reformatory, modernizing ambitions.